Financial Distress And Bank Performance: The Moderating Effect Of Capital Adequacy In Sri Lanka’s Licensed Commercial Banks - Tharshiga, P.; Chalani, M.L.N. (Jaffna Science Association, 2025)
The Altman Z-Score remains a critical tool in financial analysis, providing vital insights into a company's financial stability and resilience against economic pressures. The present study investigates the impact of financial distress on financial performance, specifically examining the moderating role of the CAR in licensed commercial banks in Sri Lanka. A quantitative methodology was employed to achieve the research objectives, utilising panel data extracted from the annual reports of thirteen licensed commercial banks in Sri Lanka, covering the period from 2014 to 2023. The Fixed Effects Model is deemed more suitable for ROE, indicating that unobserved heterogeneity substantially influences ROE, thus necessitating a model that captures firm-specific variations. Conversely, for ROA, the acceptance of the null hypothesis suggests that the Pooled Ordinary Least Squares Model is more appropriate, as it does not require firm-specific considerations. Further analysis indicates that both the Altman Z-Score and CAR exert a significant negative effect on ROE and ROA. Additionally, the interaction term between AZS and CAR demonstrates a moderating effect, with varying significance across different models. The findings of this study provide important insights into the financial performance of licensed commercial banks in Sri Lanka, with a specific focus on the impact of capital adequacy and financial distress on profitability. The use of the Fixed Effects Model for ROE emphasises the critical role of firm-specific factors, highlighting the need for banks to consider internal variations when evaluating their performance. On the other hand, the suitability of the Pooled Ordinary Least Squares Model for ROA suggests that, in some cases, broader industry factors might suffice in explaining performance trends. The nuanced moderating effect between financial distress and profitability suggests that banking strategies should avoid a one-size-fits-all approach. Instead, customised financial strategies that account for both internal characteristics and external economic conditions are needed to enhance profitability, stability, and sustainability in the Sri Lankan banking sector.
Keywords: Bank performance; Capital adequacy; Financial distress; Return on equity and return on assets